2018
DOI: 10.1101/260794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Taxonomic Profiling and Populational Patterns of Bacterial Bile Salt Hydrolase (BSH) Genes on Worldwide Human Gut Microbiome

Abstract: SummaryBile salt hydrolase (BSH) in gut bacteria can hydrolyze conjugated bile salts to unconjugated bile acids and amino acids. Thereby play a crucially important role in host health by reducing serum cholesterol levels, preserving bile acids balance and regulating various metabolism as signaling molecules. Here we present the taxonomic identification of BSHs in human microbiota and elucidate the abundance and activity differences of various bacterial BSHs among 11 different populations. For the first time, w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 40 publications
4
75
0
Order By: Relevance
“…While there is significant divergence in BSH protein sequence across gut strains, all BSHs possess a conserved active site that includes a catalytic cysteine (Cys2). 1,10 This residue performs the nucleophilic attack on the substrate carbonyl, resulting in amide bond cleavage (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is significant divergence in BSH protein sequence across gut strains, all BSHs possess a conserved active site that includes a catalytic cysteine (Cys2). 1,10 This residue performs the nucleophilic attack on the substrate carbonyl, resulting in amide bond cleavage (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study identified BSHs in gut species from 117 genera and 12 phyla, including the two dominant gut phyla, Bacteroidetes and Firmicutes, as well as Actinobacteria and Proteobacteria. 10 A non-toxic, small molecule pan-inhibitor of gut bacterial BSHs would provide a powerful tool to study how bile acids affect host physiology. Such a compound should limit bile acid deconjugation across the vast majority of gut strains without significantly affecting the growth of these bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…500We found that the abundance of several Bacteroides, Bilophila and Lachnospiraceae 501 bacteria increase during tadpole development and metamorphosis. These bacteria are well-502 known to be abundant in the gastro-intestinal tracts of numerous vertebrates, including man, 503and characterized by their resistance to high concentrations of bile salts or their bile acid 504 hydrolase activities(Song et al, 2019). We therefore propose an interpretation of our findings 505 in light of bile acids being key molecular components regulating the gut microbiome 506 composition during amphibian development and metamorphosis.…”
mentioning
confidence: 77%
“…Bile acids can act directly on the gut microbiome 512 because they have intrinsic antimicrobial activity and indirectly because their host cellular 513 receptors regulate antimicrobial peptides genes. In turn, some bacteria encode bile hydrolases 514 that enable the production of secondary bile acids(Joyce et al, 2014;Song et al, 2019). 515 Therefore, we can consider bile acid composition as a trait of strong evolutionary significance 516 since it links nutrition, gut, liver and gill physiology, host genome evolution and the gut 517 microbiome composition(Reschly et al, 2008;Hofmann et al, 2010;Ridlon et al, 2014).…”
mentioning
confidence: 99%
“…The majority of our knowledge base for food, microbes and BA metabolism comes from rodents and their translation to humans, there are considerable knowledge gaps in animal husbandry 52,53 . There are many incidences where this work does not translate, due simply to copy number classes of enzymes, fundamental metabolic differences and to signaling.…”
Section: Discussionmentioning
confidence: 99%